(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2024)
This theoretical research paper aims to aid the conceptual evolution of Grand Unified Theory (GUT), through developing the qualitative alignment of current divergent theoretical perspectives and outlier experimental evidence in the novel synthesis of a holistic new perspective through the philosophy of science context of initiating a paradigm shift in the dynamics of modern particle and dimensional physics theory. Taking the central components of Superstring and M-theory into a conceptual synthesis of theoretical dynamics and experimental evidence incorporating the four fundamental forces of nature, hyperspace theory, zero-point vacuum fluctuations of energy, the Casimir virtual particle effect, the higgs field, photoelectric radiation, quantum tunnelling, dark energy and the four dimensions of space and time in the conceptual composition of a schematic alignment of dynamic essences of physical existence formed into an eleven-dimensional subspace unification of manifest reality. Exploring the theoretical interaction of three polemics of opposed dimensional properties and essences to realities manifest nature, as intersecting dichotomously distinct and conceptually defined axis of hyperspatial essence unified through a zeropoint subspace ether of seven dimensions, an eleven dimensional theory of reality incorporating the aforementioned components as the end product is synthesised. With the desire of elaborating and expanding the qualitative and conceptual dynamics of Grand Unified Theory as a paradigm, this research paper hopes to develop a broadened theoretical context along with increasing the alignment precision and dynamic inclusivity of current divergent tangents and experimental outliers into the synthesis of a complete and comprehensive future GUT paradigm.